Elementary statistics / Allan G. Bluman - Bluman, Allan G. (Estados Unidos de América, 1995)
the nature of probability and statistics; frequency distributions and grphs
Incluye: bibliografía, imagen, índice onomástico
Col. Admon
Keywords: 1. ADMINISTRACIÓN 2. ESTADISTICA 3. PROBABILITY